Short- and long-term results after surgical treatment of an ununited anconeal process in the dog - Meyer-Lindenberg, A.; Felir, M.; Molte, I. (Veterinary and Comparative Orthopaedics and Traumatology, 2001)
In a prospective trial over seven years (1993-1999), 44 joints from 41 dogs with an ununited anconeal process are reported. The average age of the animals was 23 weeks. With regard to breed distribution, the German Shepherd was most frequently represented with 29 animals.In 35 joints, the anconeal process was stabilised with lag screw and pin, as there was no fibrous connection between the anconeal process and the ulna. Additionally, in all cases an ulna ostectomy was performed. In nine joints, the connection of the anconeal process to the olecranon was firm and only a proximal ulna ostectomy was performed. The patients were rechecked clinically and radiologically, at an average of 13 weeks post operation. With one exception, in all of the cases the apophysis was closed. The implants were removed in 25 patients. The surgical results were examined once more after an average of 20 months in 43 joints (40 dogs). 83.7% of the cases (n = 36) did not show any lameness after the combined therapy with fixation of the isolated anconeal process and osteotomy of the ulna (n = 28) or ulna ostectomy only (n = 8) and were assessed as ‘good’. Six dogs (five with fixation, one with ostectomy) showed some degree of lameness after heavy strain and were only evaluated as ‘satisfactory’. One dog still had a striking low to medium grade lameness, so that the result was regarded as ‘unsatisfactory’. With regard to the development of arthrosis, only nine of the 30 joints (30%) examined radiographically showed a mild increase of the arthroses during later examinations.In many cases excision of the ununited anconeal process leads to unsatisfactory long-term results. Frequently surgical treatment does not lead to fusion. This paper describes a concept for treatment of an ununited anconeal process and the short- and long-term results. Proximal ostectomy of the ulna was performed, as a single measure, when the anconeal process was tightly in place. In joints with a loose anconeal process, the piece of bone was stabilised with implants, in addition to an ostectomy of the ulna. After an average of three months, the anconeal process had fused with the ulna, in all hut one case. In long-term follow-ups, after an average of 20 months, most of the dogs did not show any lameness, even after exercise. In only a few joints was a minor increase of arthrosis noted. The technique described is considered to be useful to treat the ununited anconeal process in young dogs.
Keywords: Gnunited anconeal process; fixation; ulna ostectomy; long-term results